Entrance-sealing behavior in the home cage: a defensive response to potential threats linked to the serotonergic system and manifestation of repetitive/stereotypic behavior in mice - Horii-Hayashi, Noriko; Masuda, Kazuya; Kato, Taika; Kobayashi, Kenta; Inutsuka, Ayumu; Nambu, Miyu F.; Tanaka, Kazumasa Z.; Inoue, Koichi; Nishi, Mayumi (Frontiers in Behavioral Neuroscience, 2024)
The security of animal habitats, such as burrows and nests, is vital for their survival and essential activities, including eating, mating, and raising offspring. Animals instinctively exhibit defensive behaviors to protect themselves from imminent and potential threats. In 1963, researchers reported wild rats sealing the entrances to their burrows from the inside using materials such as mud, sand, and vegetation. This behavior, known as “entrance sealing (ES),” involves repetitive movements of their nose/mouth and forepaws and is likely a proactive measure against potential intruders, which enhances burrow security. These observations provide important insights into the animals’ ability to anticipate potential threats that have not yet occurred and take proactive actions. However, this behavior lacks comprehensive investigation, and the neural mechanisms underpinning it remain unclear. Hypothalamic perifornical neurons expressing urocortin-3 respond to novel objects/potential threats and modulate defensive responses to the objects in mice, including risk assessment and burying. In this study, we further revealed that chemogenetic activation of these neurons elicited ES-like behavior in the home-cage. Furthermore, behavioral changes caused by activating these neurons, including manifestations of ES-like behavior, marble-burying, and risk assessment/burying of a novel object, were effectively suppressed by selective serotonin-reuptake inhibitors. The c-Fos analysis indicated that ES-like behavior was potentially mediated through GABAergic neurons in the lateral septum. These findings underscore the involvement of hypothalamic neurons in the anticipation of potential threats and proactive defense against them. The links of this security system with the manifestation of repetitive/stereotypic behaviors and the serotonergic system provide valuable insights into the mechanisms underlying the symptoms of obsessive-compulsive disorder.